Sustainable Nipa Palm (Nypa fruticans Wurmb.) Product Utilization in Thailand - Onanong Cheablam; Boontaree Chanklap (Scientifica)
Nipa palms, a plant species in mangrove forest, are valuable and beneficial for the local community’s economy as well as the conservation in the southern region of Thailand. This study aimed to investigate the use of nipa palms in Khanap Nak and focused on the type of products made from nipa palms and the yield of this plant through focus group discussion and interview with the farmers maintaining nipa palm forest. The results suggested that nipa palms in Khanap Nak can yield for 5–100 years. Apart from the benefits to the community in terms of sustainability, as it prevents erosion, it provides sources for the production of food (molasses, granulated sugar, syrup, and vinegar from sap) and raw materials (roofing material and cigarette paper from leaves and stem), which can generate income to community members. It was found that most of the communities earn 90–130 USD/day from palm sugar production. The quantity of nipa palm products varies in each season, resulting in different prices. In this regard, they can produce high quantity of products made from sap from January to March. However, the production of different types of sugar requires local knowledge and wisdom to ensure good quality. Nipa palm production is the sustainable way to utilize mangrove forest resources, leading to effective conservation and good life quality. Regarding problems and difficulties in farming, it was found that natural disaster is a major threat, such as drought, excessive amount of salt or freshwater in certain periods, and insect pests.